OPTIMALISASI BANDUL MATEMATIS MENGGUNAKAN TRACKER DALAM PENENTUAN PERUBAHAN PERCEPATAN GRAVITASI PERMUKAAN BUMI (g) AKIBAT GERHANA MATAHARI SEBAGIAN (GMS) 9 MARET 2016 - Setyadin, Anggi Hanif; Ferahenki, Ardi Rizkia; Ramayanti, Suci; Sholihat, Fitri Nurul; Nugraha, Muhamad Gina; Saepuzaman, Duden; Samsudin, Achmad; Utama, Judhistira Arya; Susanti, Hana; Kirana, Kartika Hajar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study was conducted to determine the effect of partial solar eclipse (GMS) to the acceleration due to gravity (g) the perceived objects on the Earth’s surface. Data is collected in Bandung with the coordinates of 6Â°51’48 "S, 107Â°35’40" E for three days on 8, 9 and March 10 2016 with a span of 07.00 to 08.00 am. Earth’s surface gravitational acceleration (g) is determined from the period of a pendulum swing that moves harmonics. The instrument used is the mathematical pendulum are optimized by material type nylon rope to prevent the rotational motion of the pendulum, the use of mirrors board to identify and eliminate Conic motion of pendulum and analysis tracker for the determination of the period of a pendulum precisely. Data were collected by recording the pendulum swing using high-resolution cameras with a shooting speed of 24 frames per second (fps), the video is analyzed using application tracker in order to obtain the period of a pendulum swing. The results showed a mean value of the Earth’s surface gravitational acceleration (g) of the third day in a row is 9.81524 m s2, 9.808285 m/s2 ,and 9.813122 m/s2. Based on the results of this study concluded that the Earth’s surface gravitational acceleration (g) is influenced by partial solar eclipse. Keywords: Eclipse, Tracker, Mathematical Pendulum.